Strategi dan Peran Komunikasi Bisnis Dalam Upaya Meningkatkan Minat Beli Konsumen di Era Digital - Meyra Rizky Azhary; Muhammad Agung; Nabila Prahaski; Tuti Tri Ulin; Suhairi Suhairi (Universitas 45 Surabaya, 2023)
This article aims to investigate the tactics and functions of corporate communication in an effort to increase consumer interest in making purchases in the digital era. The research method used in this article is qualitative, meaning that it is based on readings from the literature as well as quotes from other studies and professional opinion. students study the tactics and functions of corporate communication in an effort to boost consumer interest in making purchases in the digital era. Other people can use the internet to communicate with other people who live far away, read electronic books, and conduct information searches. With the internet, humans can communicate with people far away, read digital books, search for information, and even shop online. This has influenced marketing methods from conventional to digital, and increased buying interest online.